Penguatan Literasi Masyarakat Kelurahan Winduhaji Terhadap Digitalisasi Pelayanan Publik untuk Scale-up Bisnis Skala Rumah Tangga - Iman Teguh; Oktaviani Rita Puspasari; Rizki Indrawan; Dewanto Tribuana; Ati Sumiati (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Currently, Kuningan Regency still has the highest open unemployment rate in the district government cluster in West Java. This problem can be minimized with literacy in terms of digitalization of public services to increase the scale of household businesses. Winduhaji Village was chosen as a partner with the main problem being that the majority of household business actors are still locally oriented in marketing and the majority of household business actors still do not have the importance of certificates that improve product quality. This program uses the methods of socialization, training, technology implementation and success evaluation. The program was attended by 27 participants from partners. The achievement of product marketing training success through the TikTok shop marketplace reached 100%, the achievement of the Business License Number success reached 100%, halal product certification reached 74%, brand legality reached 81.5%, BPOM certification reached 63%. Increasing Community Literacy towards the digitalization of public services needs to be continuously improved to increase the scale of household businesses, so that they are not vulnerable to poverty and reduce the level of open poverty.